Diagnostic dilemma of paraneoplastic arthritis: case series - (:unkn) unknown (WILEY-BLACKWELL, 2014)
Objectives: Paraneoplastic arthritis (PA) may mimic rheumatic diseases. While presenting the demographic and laboratory features of the patients diagnosed with PA, this study also aims to provide possible appropriate tools to differentiate the PA cases from early rheumatoid arthritis (ERA). Methods: Sixty-five patients with PA (male/female: 43/22) from 15 different rheumatology clinics and 50 consecutive patients with ERA (male/female: 13/37) fulfilling the 2010 American College of Rheumatology (ACR) criteria for the diagnosis if the RA from Gaziantep Rheumatology Early Arthritis Trial (GREAT) as controls who were diagnosed at least 12 months before, were enrolled into study. Results: Mean ages of the patients with PA and ERA were 50.2 +/- 15.3, and 42.7 +/- 12.3, respectively, and the mean ages of the patients with PA were significantly higher than the ERA. Unlike the ERA patients, in our case series PA was predominantly observed among males. Oligoarthritis was significantly higher in solid tumors in contrast to ERA (P = 0.001). Polyarthritis and symmetric arthritis were significantly higher in the ERA group in contrast to all malignancies (P = 0.001). Rheumatoid factor (RF) and anticyclic citrullinated peptide antibody (anti-CCP) positivity were significantly higher in the ERA group (each P = 0.001). Lactic dehydrogenase levels of hematologic malignancies were significantly higher than other groups (each, P = 0.001). Conclusions: ERA patients had more symmetric joint involvement than PA; laboratory markers could be also an alternative where there is high RF and anti-CCP positivity with antibody levels among the ERA patients. Finally, the demographic features can be used as differentiating
Keywords: early rheumatoid arthritis; malignancy; paraneoplastic arthritis; RHEUMATIC MANIFESTATIONS; POLYARTHRITIS; LEUKEMIA; PATIENT; SYMPTOM; CANCER; PAIN